La confiabilidad de las evaluaciones del aprendizaje conceptual: Índice Spearman-Brown del método split-halves = Reliability of the evaluation of conceptual learning: index of Spearman-Brown and the split-halves method. - Rositas, J.; Badii Zabeh, Mohammad Hosein; Castillo, J. (Universidad Autónoma de Nuevo León, 2006)
Abstract. Based upon the curiosity to evaluate in a reliable and consistent fashion, the acquisition of knowledge, several methods of evaluating conceptual learning are presented, and among these, the method of Index of Spearman-Brown within the split-halves method is used for the estimation of the reliability of the measurement instrument. The related problems in this respect are laid out, taking into account the ease of determination of this index in a practical manner with the aid of the concrete applied cases. Final considerations are raised with regards to application of this methodology in the USA and the New Zealand. Finally, the utilization of these methods are encouraged.